FixK2 Is the Main Transcriptional Activator of Bradyrhizobium diazoefficiens nosRZDYFLX Genes in Response to Low Oxygen - Torres, María J.; Bueno, Emilio; Jiménez-Leiva, Andrea; Cabrera, Juan J.; Bedmar, Eulogio J.; Mesa, Socorro; Delgado, María J. (Frontiers in Microbiology, 2017)
The powerful greenhouse gas, nitrous oxide (N2O) has a strong potential to drive climate change. Soils are the major source of N2O and microbial nitrification and denitrification the main processes involved. The soybean endosymbiont Bradyrhizobium diazoefficiens is considered a model to study rhizobial denitrification, which depends on the napEDABC, nirK, norCBQD and nosRZDYFLX genes. In this bacterium, the role of the regulatory cascade FixLJ-FixK2-NnrR in the expression of napEDABC, nirK and norCBQD genes involved in N2O synthesis has been previously unravelled. However, much remains to be discovered regarding the regulation of the respiratory N2O reductase (N2OR), the key enzyme that mitigates N2O emissions. In this work, we have demonstrated that nosRZDYFLX genes constitute an operon which is transcribed from a major promoter located upstream of the nosR gene. Low oxygen was shown to be the main inducer of expression of nosRZDYFLX genes and N2OR activity, FixK2 being the regulatory protein involved in such control. Further, by using an in vitro transcription assay with purified FixK2 protein and B. diazoefficiens RNA polymerase we were able to show that the nosRZDYFLX genes are direct targets of FixK2.